الثقة بالنفس وعلاقتها بمفهوم الذات لدى تلاميذ التعليم الأساسي بولاية النيل الابيض - اشرف محمد احمد على (White Nile Journal for Studies and Research, 2015)
The study aimed at investigating the general characteristic of self-confidence among basic level, as well as investigating the correlation between self-confidence and self-esteem. It is also dealt with discrepancy in self-confidence among the pupils due to gender variables. The study sample consisted of (400) pupils in basic stage (200 boys besides 200 girls). The researcher has randomly selected the research - sample. He used self-esteem and self confidence scales. The data has been treated by statistical methods. such as Pearson's correlation coefficient and (T) test. The study came to the following results: The general characteristics, regarding, self confidence among basic stag pupils are high. - There correlation between self confidence and self esteem among basic stage pupils. 3-There are statistical significance difference among basic stage pupils due to gender variable in favor of males.